The influence of thickness of ACL tendon graft on long-term results of treatment - Piotr Piech; Paweł Polak; Maciej Kozioł; Paweł Obierzyński; Grzegorz Staśkiewicz; Małgorzata Neścior (Kazimierz Wielki University, 2018)
1. INTRODUCTION: Operative treatment is the treatment of choice for the most severe, third-degree ACL sprain. Many operational techniques exist, including technique using a quadruple-folded semitendinosus tendon and the technique of double-folded semitendinosus and gracilis tendons. Depending on the technique chosen, we can obtain different thicknesses of the grafts used.   2. AIM OF THE STUDY: To find a relationship between the type of surgical technique used and the thickness of the graft, as well as to assess the effect of the thickness of the applied autograft on the long-term outcome of the treatment.   3. MATERIALS AND METHODS: A retrospective study included a group of 43 patients operated on due to ACL injury. In 21 patients, the procedure was performed using the quadruple-folded semitendinosus tendon, whereas in 22 patients the procedure was performed using double-folded semitendinosus and gracilis tendons. The patients were divided into groups based on the thickness of the transplant. A special questionnaire prepared on the basis of the KOOS scale was used to assess the subjective performance of the knee. The type and thickness of the graft was determined based on the analysis of operational protocols. The statistical analysis of the results of the study was performed. The Chi-square compatibility test or chi-square compatibility test in the Yates modification were used to assess the relationship.   4. RESULTS: A relationship was found between the parameters: "general quality of life" (p = 0.01), "pain" (p = 0.005), "sports activity" (p = 0.05), "everyday activities" (p = 0, 01). There is no dependence for the "other symptoms" parameter (p = 0.1). There is no relationship between the technique used and the graft thickness (p = 0.2).    5. CONCLUSIONS: The choice of the surgical technique does not affect the final thickness of the autograft. Overall quality of life, pain, sports activity; everyday activities are the parameters of the KOOS scale, which are affected by the thickness of the transplant.